CLIL in German Lessons for Indonesian German Teachers to Achieve The SGDs - Dewi Kartika Ardiyani; Primardiana Hermilia Wijayati; Edy Hidayat; Dudy Syafruddin (International Journal of Pedagogical Language, Literature, and Cultural Studies (i-Plural), 2024)
This paper aims to solve the problem of the lack of use of German language in German lessons and the lack of mastery of material and didactic methodological competence of Indonesian German teachers through the implementation of Content and Language Integrated Learning (CLIL). The method used is to conduct a CLIL-based lesson using prepared prototypes in the workshops, conduct observations during implementation, collect interview data, evaluate and discuss work results. The workshop participants and respondents of this research were Indonesian German teachers. The results of this study show that CLIL can be implemented well and smoothly. By implementing CLIL, German teachers' mastery of materials and didactic methodological competence can be improved, making learning German more interesting and enjoyable. Ultimately, we can contribute to the efforts to achieve SDG target 4, namely quality education.